Migration and Labour Market Differences : The Case of Wales - Stephen Drinkwater; David H. Blackaby (Institute for the Study of Labor (IZA), 2004)
The migration of labour can affect economies in several ways. This paper focuses on two of the economic impacts of migration in the context of the recent Welsh experience. Firstly, since migration is a key aspect of labour market flexibility, it is a mechanism through which local and regional labour market differences can be reduced. However, it is found that the most deprived parts of Wales have the lowest levels of migration and that both in and outmigration rates are negatively correlated with unemployment and sickness rates. Secondly, the characteristics of in and out-migrants have important implications for the current and future performance of local and regional economies. Using a variety of data sources, it is shown that people leaving Wales are younger and more educated than migrants to Wales. Furthermore, younger and more educated Welsh individuals appear to have a higher willingness to move than their counterparts living elsewhere in Britain.
Keywords: R23; J61; 330; migration; local and regional labour markets; Wales; Regionale Arbeitsmobilität; Binnenwanderung; Regionaler Arbeitsmarkt; Wales; Grossbritannien